PELAYANAN PASTORAL BAGI LANSIA DI GKPI PAGAR SINONDI DAN HKBP PARDOMUAN SILANGKITANG - Ditarya Siahaan (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractThe existence of the elderly should be one of the focus of Church pastoralministry. The elderly is a final stage of life and at this stage there are a lot of problems that may be experienced and felt by them. Changes in the aging process carry some psychological impacts on the elderly which cause them to often feel loneliness, emptiness, fear, depression, and also have a life dependency on others. The church should be struggling on this problem and doing pastoral care for them.Keywords: Service, Pastoral, Church, Elderly, Loneliness, Emptiness,HKBP Pardomuan, GKPI Pagar Sinondi